2019
DOI: 10.1111/gcb.14741
|View full text |Cite
|
Sign up to set email alerts
|

Weakened growth of cropland‐N2O emissions in China associated with nationwide policy interventions

Abstract: China has experienced rapid agricultural development over recent decades, accompanied by increased fertilizer consumption in croplands; yet, the trend and drivers of the associated nitrous oxide (N2O) emissions remain uncertain. The primary sources of this uncertainty are the coarse spatial variation of activity data and the incomplete model representation of N2O emissions in response to agricultural management. Here, we provide new data‐driven estimates of cropland‐N2O emissions across China in 1990–2014, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 63 publications
1
46
0
1
Order By: Relevance
“…Various models may be used to account for scale or leakage effects such as indirect land-use changes (Qin et al, 2016). The methods currently available include datadriven approaches based on worldwide measurement networks (Shang et al, 2019), statistical or empirical flux-upscaling models (Shang et al, 2019;Wang et al, 2019), process-based models and, lastly, integrated assessment models (IAM;Zomer et al, 2016).…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…Various models may be used to account for scale or leakage effects such as indirect land-use changes (Qin et al, 2016). The methods currently available include datadriven approaches based on worldwide measurement networks (Shang et al, 2019), statistical or empirical flux-upscaling models (Shang et al, 2019;Wang et al, 2019), process-based models and, lastly, integrated assessment models (IAM;Zomer et al, 2016).…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Various models may be used to account for scale or leakage effects such as indirect land‐use changes (Qin et al, 2016). The methods currently available include data‐driven approaches based on worldwide measurement networks (Shang et al, 2019), statistical or empirical flux‐upscaling models (Shang et al., 2019; Wang et al., 2019), process‐based models and, lastly, integrated assessment models (IAM; Zomer et al., 2016). Process‐based models include a representation of N cycling processes, which are an essential tool in assessing and predicting the terrestrial N cycle and N 2 O fluxes in response to multi‐factor global changes.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…N fertilizer-induced direct N 2 O emissions from agricultural fields are critically affected by many factors, including N application rate, climate variables, crop types and soil characteristics [21,[23][24][25][26]. Several models have been developed and used to estimate N fertilizerinduced N 2 O emissions from the soil [25,27,28]. Due to limited availability of enough relevant information, the determination of direct N 2 O emissions from synthetic N fertilization for wheat and maize in China in the current work was done using the IPCC emission factor method combined with region-and crop-specific direct N 2 O emission factors.…”
Section: Discussionmentioning
confidence: 99%
“…China is now on the right track to implement improved N management techniques in croplands, which would help to identify options for lowering GHG emissions from agricultural production. In recent years, N 2 O emissions from Chinese croplands have grown slowly, owing to nationwide policy interventions and prevalence of technological adoptions [28,42,43]. Moreover, technological innovation in China's N fertilizer industry could make a significant contribution to synthetic N manufacture-related GHG emissions reduction [10].…”
Section: Discussionmentioning
confidence: 99%
“…A recent global assessment using ensemble of terrestrial biosphere models also found that global N fertilizer application contributes 2.0 ± 0.8 Tg N 2 O-N yr -1 during 2007-2016, manure application contributes 0.6 ± 0.4 Tg N 2 O-N yr -1 , and N deposition contributes 26% of global soil N 2 O emission (Tianet al 2019). Furthermore, the deceases in cropland-N 2 O emissions after 2003 are mainly ascribed to the reduction in usage of N fertilizer in China (Shang et al 2019). Therefore, we hypothesized that soil N contents might play an important role on regulating soil N 2 O emissions at the global scale.…”
Section: Introductionmentioning
confidence: 99%